Putting National Pharmacare on the Federal Agenda - Michel Grignon; Christopher J. Longo; Gregory Marchildon; Stephen Officer (McMaster University Library Press, 2019)
In June 2018, the Federal Government of Canada created an Advisory Council on the Implementation of National Pharmacare, scheduled to report one year later on the best strategy to implement such a program and give Canadians access to affordable prescription drugs outside of the hospital. The current state of coverage through employer-sponsored plans and public plans conditional on income and age is increasingly perceived as unfair and inefficient. The Council used a mixture of expert consultations, an online survey and discussion forums for the general public to explore three options: a universal public plan, a catastrophic spending plan, or a patching of current coverage to include the non-covered. Creating such a Council was seen by the government as a solution for navigating a complex policy problem with difficult federal-provincial dimensions. Le gouvernement fédéral canadien a créé en juin 2018 un Conseil consultatif sur la mise en œuvre d'un régime national d'assurance médicaments, dont le rapport sur la meilleure stratégie pour mette en œuvre un tel régime et permettre aux Canadiens d'accéder à des médicaments abordables hors de l'hôpital est attendu un an après. La situation présente couvrant les individus à travers une combinaison de plans d'employeurs et de plans publics sous condition de revenu et d'âge est de plus en plus perçue comme injuste et inefficace. Le Conseil devra donc explorer trois options, en s'appuyant sur des consultations d'experts, un sondage en ligne, et des forums de discussion pour le grand public : un régime public universel, un régime couvrant les dépenses catastrophiques, et un régime modeste offert à ceux n'ayant pour l'instant aucune couverture. La création de ce Conseil était vue par le gouvernement comme une solution pour négocier une question délicate affectant l'équilibre des prérogatives provinciales et fédérales.